FACTORS AFFECTING STUDENTS, ASSESSMENTS PERFORMANCE: CASE OF KENYA MEDICAL TRAINING COLLEGE (AN OPERATIONAL STUDY OF KMTC) - Owuor, Collins; Tshombe, Dorothy; Musuya, Alloys; Otieno, Grace (African Journal of Education and Practice, 2021)
Purpose: The study assessed the influence of both intrinsic and extrinsic factors and students perceptions. While student and teacher-related factors constitute the intrinsic factors, parents and the government on the other hand are examples of the extrinsic factors. This research project focuses on assessing the factors that contribute and influence KMTC students' performance with an aim of establishing ways to improve their performances in examinations and assessments. Methodology: A mixed and descriptive cross-sectional research design was utilized involving a study of both intrinsic and extrinsic factors that affect students' performance. Findings: The study findings established that both intrinsic and extrinsic had an effect on performance. The study findings established that a unit increase in student attitude can lead to an increase of 0.05 in the scores of student performance. This implies that student attitude had a significant positive effect on student performance. The study found out that a unit increase in intrinsic factors of 0.227 can lead to an increase in students' performance. This clearly shows that extrinsic factors had a significant positive effect on student performance. The study results revealed that a unit increase of 0.01 can lead to an increase in students' performance. This shows that extrinsic factors had a significant positive effect on students' assessment and performance. Therefore, the study independent variables had a strong positive relationship to the dependent variable which was student performance. Unique contribution to theory, practice and policy: The study recommends for higher learning institutions to integrate both intrinsic and extrinsic factors in their planning. Key Words: Multiple Choice Questions- Multiple choice questions are questions where the respondent is given a variety of options to pick from while answering, Objective Structured Clinical Examination- it is an examination structured to meet certain specific objectives and in this case OSCEs are particularly used in the assessment of clinical officers, Assessment-it refers to the various methods and tools that educators employ in evaluation, measurement and documentation of academic readiness, learning progress, skills acquisition and education needs of a student; Intrinsic factors- refers to those factors that exists within the system (KMTC), they form the internal drive to objectives and cannot be separated from the system. E.g. in KMTC, intrinsic factors includes students' factors, lecturer factors, institutional factors e.t.c.; Extrinsic factors- refers to those factors that operate outside the system (KMTC) to influence the achievement of an objective. These factors are external and separate entities from the system but have established mutual connections e.g. the government, parents, employers' e.t.c